STUDY OF PREFRONTAL OXYGENATION DURING EMOTIONAL THINKING USING FUNCTIONAL NEAR-INFRARED SPECTROSCOPY (FNIRS) - Kazem, Zaharaa Mohammed; Taleb, Ayat Hamid; Al-Hassan, Murtdha falah Abd; Hussein, Muqtada hussam; Naji, Noor hassan; Ali, Tuqa Ihsan Abd; Rahman, Mahir (PT. Antis International Publisher, 2024)
Introduction: This section provides an overview of the project and introduces the topic. It should include the background, objectives, and scope of the research. Literature Review: This section reviews relevant literature related to the topic to provide a better understanding of the existing research and technology available. It should include sources such as books, academic journals, and online articles. Methodology: This section outlines the methodology used to design and develop the project, including the hardware and software components, programming languages and tools used, and testing procedures. System Design: This section describes the architecture and design of the system, including the hardware and software components, communication protocols, and interfaces. It should provide a detailed explanation of how the system is structured. Implementation: This section details the process of implementing the system, including the setup of the hardware and software components, programming of the microcontroller and sensors, and integration of any external platforms. Results and Evaluation: This section presents the results of the testing and evaluation of the system, including the performance, efficiency, and effectiveness of the system in achieving its objectives. It should also discuss any limitations or challenges encountered during testing. Conclusion and Future Work: This section summarizes the research findings and provides recommendations for future work. It should discuss any potential for further development and improvement of the system.